2019
DOI: 10.1002/pa.2010
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment, information and communication technology, trade, and economic growth in the South Asian Association for Regional Cooperation countries: An empirical insight

Abstract: Information and communication technology (ICT) is one of the key sectors promoting economic growth in the present modern era of globalization. It promotes technological advances in global communications as well as production techniques and contributes to economic growth and development. Most of the economic activities, including international trade and foreign direct investment (FDI), are largely dependent on various modern sources of ICT. The objective of this study is to examine the dynamic relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…They explain that in developed countries, the improvement in ICT causes an increase in FDI; however, in developing countries, the causality direction runs from FDI to ICT. Bhujabal and Sethi (2019) investigated the dynamic links between ICT, FDI, trade, and GDP by applying various panel estimates. They provided evidence of a long term relationship between FDI and other variables.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They explain that in developed countries, the improvement in ICT causes an increase in FDI; however, in developing countries, the causality direction runs from FDI to ICT. Bhujabal and Sethi (2019) investigated the dynamic links between ICT, FDI, trade, and GDP by applying various panel estimates. They provided evidence of a long term relationship between FDI and other variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of these studies have shown that FDI and international trade increase as the Internet use rate increases (Choi, 2003; Ko, 2007; Tay, 2015; Yousefi, 2018), while other studies acknowledge that the growth in trade and FDI stimulates Internet use (Ketteni et al, 2015; Shirazi et al, 2010). In addition, some scholars identify a two-way causal relationship between the Internet and FDI (Gholemi et al, 2006; Leitão and Baptista, 2011), and between trade and the Internet (Bhujabal and Sethi, 2019). However, very few studies have combined the Internet with economic factors (e.g., FDI, imports, exports, and GDP) in a panel vector autoregressive (VAR) model that focuses on Asia.…”
Section: Introductionmentioning
confidence: 99%
“…From a more academic point of view, it is possible to find researchers who stress the importance of ICT to achieve sustainable growth objectives. For example, Bhujabal & Sethi (2019) [31] (pp. 1-2) point out a number of benefits derived from ICT, among which we highlight: (a) global integration, which allows developing countries to adopt and benefit from the technologies of developed countries, (b) the ability of these technologies to overcome both geographical and cultural barriers, which promotes convergence between advanced and non-advanced economies, (c) promotion of government transparency by reducing corruption, and (d) access to new opportunities and information for the population.…”
Section: Ict and Sustainable Environmentmentioning
confidence: 99%
“…Le (2017) showed similar results in his study on Vietnam’s trade inflow of FDI. Afterward, the literature regarding FDI has an essential and leading role in the expansion of developed and developing economies (Bhujabal, 2019). FDI occurs when an investor of one country (home country) has acquired an asset in another country (host country), intending to manage the acquired asset (World Trade Organization, 1996).…”
Section: Introductionmentioning
confidence: 99%